2023
DOI: 10.1042/cs20220284
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the development of severe fetal growth restriction

Abstract: Fetal growth restriction (FGR), which most commonly results from suboptimal placental function, substantially increases risks for adverse perinatal and long-term outcomes. The only “treatment” that exists is delivery, which averts stillbirth but does not improve outcomes in survivors. Furthermore, the potential long-term consequences of FGR to the fetus, including cardiometabolic disorders, predispose these individuals to developing FGR in their future pregnancies. This creates a multi-generational cascade of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…Syndecan1 (SDC1) is one of the most important glycocalyx proteoglycans. 8,9 It is highly localized in the syncytiotrophoblasts of chorionic villi and regulates cell signaling by forming a complex with the Vascular Endothelial Growth Factor (VEGF) receptor. SDC1 plays a role in processes such as regulation of vascular permeability, release of nitric oxide, modulation of vascular tone and blood coagulation by regulating VEGF signaling and plays an important role in endothelial cell migration, embryonic development, tumorogenesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syndecan1 (SDC1) is one of the most important glycocalyx proteoglycans. 8,9 It is highly localized in the syncytiotrophoblasts of chorionic villi and regulates cell signaling by forming a complex with the Vascular Endothelial Growth Factor (VEGF) receptor. SDC1 plays a role in processes such as regulation of vascular permeability, release of nitric oxide, modulation of vascular tone and blood coagulation by regulating VEGF signaling and plays an important role in endothelial cell migration, embryonic development, tumorogenesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has functions such as ensuring the integrity of the tissue, preventing the adhesion of leukocytes and platelets and antithrombotic activation. Syndecan1 (SDC1) is one of the most important glycocalyx proteoglycans 8,9 . It is highly localized in the syncytiotrophoblasts of chorionic villi and regulates cell signaling by forming a complex with the Vascular Endothelial Growth Factor (VEGF) receptor.…”
Section: Introductionmentioning
confidence: 99%
“…In the following weeks, vascular remodeling results in increased perfusion, resulting in improved oxygen and nutrient delivery to the placenta and fetus. Impaired oxygen delivery to the placenta or fetus, such as in cases of maternal hypoxemia or placental insu ciency, can result in severe pregnancy complications, including intrauterine growth restriction (IUGR), developmental anomalies, or fetal demise (2,3). Measurements of fetal or placental oxygen delivery would be useful to evaluate fetal exposure to a hypoxic environment this would also allow for distinguishing between cases of constitutional smallness versus IUGR due to placental insu ciency and other complications of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…IUGR is defined as a fetus that has failed to reach its growth potential, which can be due to several conditions, but is primarily caused by placental insufficiency and is characterized by impaired oxygen and nutritional supply [17,18]. The underlying cellular and molecular mechanism of fetal growth restriction is still not fully investigated [17,19]. Placentalmediated fetal growth restriction arises mainly from maldevelopment of the placental vascular system [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that impaired fetoplacental angiogenesis is associated with fetal growth restriction [21,22]. Furthermore, recent research investigated novel integrin-extracellular matrix interactions that regulate placental angiogenesis in severe fetal growth restriction [19]. However, further research is needed to investigate the underlying cause of fetal growth restriction as well as prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%